Ovary Proteome Analysis Reveals RH36 Regulates Reproduction via Vitellin Uptake Mediated by HSP70 Protein in Hard Ticks - Wang, Fangfang; Wang, Yanan; Wang, Guanghua; Zhang, Houshuang; Kuang, Ceyan; Zhou, Yongzhi; Cao, Jie; Zhou, Jinlin (Frontiers in Cellular and Infection Microbiology, 2020)
Ticks are blood-sucking vector arthropods, which play an important role in transmitting pathogens between humans and animals. RH36 is an immunomodulatory protein expressed in the salivary glands, but not other organs, of partially fed Rhipicephalus haemaphysaloides ticks, and it reaches its peak on the day of tick engorgement. RH36 gene silencing inhibited tick blood feeding and induced a significant decrease in tick oviposition, indicating that another function of immunosuppressor RH36 was regulating tick reproduction. Why did RH36 protein expressed uniquely in the salivary gland regulate tick reproduction? RH36 regulated positively the expression of vitellogenin in ovary, which indicated RH36 protein played an important role in the integration of nutrition and reproduction. According to proteomic analysis, heat shock protein 70 (HSP70) was significantly down-regulated in the immature ovary of post-engorged ticks. In addition, gene silencing of HSP70 not only inhibited tick blood-sucking and the expression of vitellogenin, but also increased tick death rate. These results suggested RH36 affected tick vitellogenin uptake and then regulated ovary cell maturation by modulating the expression of HSP70 protein, and finally controlled tick oviposition.